Comparing long-term results of endovascular intervention and coronary bypass surgery in five-year follow-up - V. G. Seyidov; A. Yu. Fisun; V. V. Evsyukov; I. V. Lyubchu; S. E. Bobyrev; E. V. Arutyunov (Российский кардиологический журнал)
A comparison of long-term angioplasty vs coronary bypass surgery results, together with assessment of dyslipidemia, diabetes mellitus, and systemic inflammation effects on recurrent angina rate, was performed during a five-year follow-up period. In 1989-2005, long-term results for 793 coronary bypass patients and 272 angioplasty patients, followed up for 5 years, were analyzed. Statistical analysis was performed with Analysis ToolPak - VBA. Comparing to in-hospital period, in 5 years after the intervention, the number of patients with recurrent angina substantially had increased. Long-term recurrent angina rates were influenced by increased levels of total cholesterol, low-density lipoprotein cholesterol, alpha-lipoprotein, C-reactive protein, and diabetes mellitus. Comparing to conservative treatment, intervention was associated with quality of life improvement, decreased angina rate and mortality. During five-year follow-up, endovascular re-intervention is as effective as coronary bypass surgery, but the need for possible 2-6 angioplasty should be taken into account.